Highly active MgO catalysts for hydrogenation of levulinic acid to γ-valerolactone using formic acid as the hydrogen source - Sultana, Asima; Lomate, Samadhan; Fujitani, Tadahiro (Frontiers in Energy Research, 2023)
This study presents an evaluation of catalytic performance of unsupported simple oxide catalysts with varying acid-base properties for the vapor phase hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL) using formic acid (FA) in an aqueous medium. Among the different oxides tested MgO catalyst is found to be highly active. Between the MgO prepared by different methods and commercially obtained, the MgO-UBE showed 100% LA conversion and 100% selectivity to GVL at 270°C. The MgO-UBE catalyst favorably allowed the production of γ-valerolactone in the presence of 50 wt% water relative to the amount of a mixture of levulinic acid and formic acid. Based on the catalytic activity and characterization results, it was concluded that the presence of Mg (OH)2 and a higher number of Lewis acid-base pair sites, Mg2+LCO2−LC are needed to achieve high LA conversion and selectivity to GVL.